The Quality of Beef Meatballs Using Soybean Flour to Increase Dietary Fiber - Meherung, Dyon; Sondakh, Erwin Hubert Barton; Pontoh, Juliance; Tuwaidan, Leonard (PT FORMOSA CENDEKIA GLOBAL, 2024)
The aim to this study was to determine the composition of soy flour and tapioca flour in making meatballs on the physical and dietary fiber quality. The materials used in this study were soy flour, tapioca flour, beef, spices. The equipment used was a mill, gas stove, oven, refrigerator, digital scales, carper press, two glass plates with different thicknesses, weights, whatman 41, pH meter, fiber sheath. This study used a ompletely andomized esign (CRD) with 4 treatments and 4 replications. The treatments consisted of R1 = 100% tapioca flour: 0% soy flour; R2 = 85% tapioca flour: 15% soy flour; R3 = 70% tapioca flour: 30% soy flour; R4 = 55% tapioca flour: 45% soy flour. The variables measured consisted of moisture, pH, water binding capacity, and crude fiber and were analyzed using analysis of variance with a completely randomized design in one-way pattern and continued with Duncan's New Multiple Range Test for significant variables. The results showed that the addition of soybean flour up to 45% did not affect the pH value and water content (P>0.05), in meatball products fortified with soybean flour. The addition of soybeans with different levels gave a significant difference (P<0.05) to the water binding capacity value of meatballs and there was an increase in the administration of 30-45%. Likewise, the dietary fiber of beef meatballs, there was an increase along with the addition of soybean flour. Based on the results of the research data and discussion, it can be concluded that 85% tapioca flour added with 15% soybean flour can increase dietary fiber in beef meatball products.